2021
DOI: 10.1038/s41598-021-97529-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on polyethylene-based carbon fibers obtained by sulfonation under hydrostatic pressure

Abstract: Polyethylene based carbon fibers were studied using high density polyethylene(HDPE) fibers and linear low density polyethylene(LLDPE) fibers with various melt flow index. The draw ratio of the polyethylene fibers and the sulfonation mechanism were investigated under hydrostatic pressures of 1 and 5 bar in the first time. The influence of the melt flow index of polyethylene and types of polyethylene fibers on the sulfonation reaction was studied. Carbon fibers were prepared through the sulfonation of LLDPE fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…After the reaction for 2 h, the fiber diameter slightly changes to 21.6 μm and remains relatively constant after 12 h of sulfonation. Interestingly, our result varies from a recent work studying a variety of PE-based fibers under similar chemical treatments, which observed that all low-density PE fibers exhibited increases in the fiber diameter at increased reaction times up to 25% of the original diameter . Other works also demonstrate a similar phenomenon in PE fibers under proper reaction conditions. , We attributed this difference to the use of sulfuric acids with different concentrations, where the diluted ones are known to be significantly more reactive than their concentrated counterparts.…”
Section: Resultscontrasting
confidence: 71%
“…After the reaction for 2 h, the fiber diameter slightly changes to 21.6 μm and remains relatively constant after 12 h of sulfonation. Interestingly, our result varies from a recent work studying a variety of PE-based fibers under similar chemical treatments, which observed that all low-density PE fibers exhibited increases in the fiber diameter at increased reaction times up to 25% of the original diameter . Other works also demonstrate a similar phenomenon in PE fibers under proper reaction conditions. , We attributed this difference to the use of sulfuric acids with different concentrations, where the diluted ones are known to be significantly more reactive than their concentrated counterparts.…”
Section: Resultscontrasting
confidence: 71%
“…For all carbonized samples, the averaged fiber diameter is ∼12 μm (Figure (G–J), indicating an ∼25% shrinkage from their original state. The reduced fiber diameter upon carbonization was slightly larger than those from multiple reports that used a similar process to produce carbon fibers from linear low-density PE …”
Section: Resultsmentioning
confidence: 61%
“…The reduced fiber diameter upon carbonization was slightly larger than those from multiple reports that used a similar process to produce carbon fibers from linear low-density PE. 60 While fibril structures are maintained after cross-linking and carbonization steps, microporosity can be developed within PP-derived carbon. For example, several previous studies found that insufficient cross-linking from a short reaction time can result in hollow carbon fibers.…”
Section: Resultsmentioning
confidence: 99%
“…PAN-based BCP can result in nitrogen-doped mesoporous carbon with nitrogen content up to 13 at% 22 , enabling their exceptional performance for many applications, such as fast-charging batteries 59 , supercapacitors 60 , and water desalination 61 . Sulfonation-enabled crosslinking of PE and PP can result in high sulfur contents, approaching 3 at% as determined through X-ray photoelectron spectroscopy (XPS) in previous reports 62 . For our system, XPS results (Fig.…”
Section: Resultsmentioning
confidence: 75%